A facile and fast method for the functionalization of polymersomes by photoinduced cycloaddition chemistry - Nallani, Madhavan (2013)
Polymersomes are promising platforms for use in biosensing, where their stability may be crucial over that of liposomes. For the introduction of the desired functionality multiple strategies have been reported for functionalization of polymersomes. However, none of them have combined readily available starting materials, facility and in situ quantification. We show a simple 4-step method for functionalization of polymersomes starting from commercially available materials. For the key conjugation step a recently explored light induced cycloaddition was used which is relatively fast (15 min) and allows in situ quantification by the intrinsic fluorescence of the conjugate. The facility of the protocol, the ease of preparation and quantification make this ‘click’-type conjugation method a promising alternative to the established strained cycloadditions.